2004
DOI: 10.1177/026988110401800308
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Action of Aripiprazole Predicts Clinical Efficacy and a Favourable Side-Effect Profile

Abstract: The antipsychotic efficacy of aripiprazole is not generally associated with extrapyramidal symptoms, cardiovascular effects, sedation or elevations in serum prolactin that characterize typical or atypical antipsychotics. The aim of this study was to clarify the mechanism of action of aripiprazole that underlies its favourable clinical profiles. The preclinical efficacy and side-effect profiles of aripiprazole were evaluated using several pharmaco-behavioural test systems in mice and rats, both in vivo and ex v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
67
0
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 129 publications
(75 citation statements)
references
References 40 publications
5
67
0
3
Order By: Relevance
“…This makes its unlikely that our failure to observe 5-HT 2 occupancy is a methodological or technical effect, and questions whether 5-HT 2 receptors in this species makes a major contribution to the pharmacological effects of aripiprazole in CAR and CAT models on acute administration. Our findings with respect to aripiprazole's 5-HT 2 receptor occupancy are also supported by the fact that in an in vivo model of 5-HT 2 antagonism (MDMT-induced head twitches in mice), aripiprazole exhibited weak inhibition at comparable doses (Hirose et al, 2004). The divergence between in vitro vs in vivo D 2 /5-HT 2 ratios could be often explained by the presence of active metabolites which in turn have different receptor affinity profiles.…”
Section: Discussionsupporting
confidence: 76%
“…This makes its unlikely that our failure to observe 5-HT 2 occupancy is a methodological or technical effect, and questions whether 5-HT 2 receptors in this species makes a major contribution to the pharmacological effects of aripiprazole in CAR and CAT models on acute administration. Our findings with respect to aripiprazole's 5-HT 2 receptor occupancy are also supported by the fact that in an in vivo model of 5-HT 2 antagonism (MDMT-induced head twitches in mice), aripiprazole exhibited weak inhibition at comparable doses (Hirose et al, 2004). The divergence between in vitro vs in vivo D 2 /5-HT 2 ratios could be often explained by the presence of active metabolites which in turn have different receptor affinity profiles.…”
Section: Discussionsupporting
confidence: 76%
“…However, we cannot exclude that pharmacokinetic peculiarities of some of these drugs (such as slow brain penetration or else: see below) may explain the fact that little or no catalepsy was observed under our experimental conditions (ie observation 1 h after drug administration). In fact, it has been reported that the maximum catalepsy response to aripiprazole occurred at 8 h postadministration (Hirose et al, 2004). This is an interesting observation, considering that in both rats and humans, a major metabolite of aripiprazole is a pure dopamine D 2 antagonist (Lawler et al, 1999), which may mitigate the D 2 receptor partial agonist properties of aripiprazole.…”
Section: Antipsychotic Activity Of the New Generation Of Antipsychotimentioning
confidence: 79%
“…Aripiprazole has a novel pharmacological profile; partial agonism at dopamine D 2 and D 3 and serotonin 5-HT 1A receptors, and antagonism at 5-HT 2A receptors. [1][2][3][4][5] Aripiprazole has been shown to improve symptoms of acute mania in placebo-controlled studies 6,7 and was superior to placebo in maintaining efficacy for up to 100 weeks in patients with bipolar mania. 8,9 This study used a randomised placebo-controlled study design and included an active haloperidol reference arm to evaluate the acute and continued efficacy of aripiprazole monotherapy in patients with bipolar disorder experiencing acute manic or mixed episodes (trial registration NCT00097266).…”
mentioning
confidence: 99%